Letter : Spanish Children's Fund (Basque Children) - Hillis, I.
037-0098-001 p.c. ack 29.6.37 Telegraphic Address: "BISAKTA, KINCROSS, LONDON." Telephone: TERMINUS 6691, 6692, 6693 THE British Iron, Steel, and Kindred Trades Association Central Office - Swinton House, 324 Gray's Inn Road (nr. King's Cross), London, W.C.1. Branch Secretary's Address- 69 MAIN ST RYECROFT nr ROTHERHAM Reference SPANISH CHILDREN'S FUND (BASQUE CHILDREN) PHOENIX WORKS JOINT COMMITTEE Branch June 28 / 1937 (SIR WALTER CITRINE.) Dear Sir, I have your communication of the 24th inst to hand for which I thank you. With regard to the monthly collections on behalf of above reference, I will bring this matter before our Committee next Saturday Evening (the 3rd of July) and I fully expect that they will fall into line with your suggestion of me taking charge of the whole of the monies. With reference to this month's collections, I am afraid I cannot alter this, but I promise you I will do my best to carry out your suggestions from July. Respectfully yours I. Hillis (Secretary) 292/946/37/98